2009
DOI: 10.1016/j.visres.2009.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, viewing distance and target complexity on static ocular counterroll

Abstract: The ocular counterroll (OCR) reflex generates partially compensatory torsional eye movements during static head roll tilt. We assessed the influence of age, viewing distance and target complexity on the OCR across the age span (13-63 years; n=47), by recording eye movements during head-on-body roll tilt (0+/-40 degrees in 5 degrees steps) while subjects viewed simple vs. complex targets at 0.33 and 1m. We found that subjects > or = 31 years had lower gains than those < or =30 years, but only for far targets. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…To test whether OCR is abnormal in skew deviation, we first sought to clarify the effects of age and target characteristic on OCR gain in a normal population across the age span (n ¼ 60). We found that OCR gain is dependent on age, viewing distances, and target complexity, 19 as well as whether the target is head fixed or earth fixed. 20 Using an earth-fixed complex target at a distance of 1 m that has been shown to elicit higher gain in normal subjects, we recorded the eye movements of 18 patients with skew deviation and 18 normal participants by scleral search coil.…”
Section: Skew Deviationmentioning
confidence: 81%
“…To test whether OCR is abnormal in skew deviation, we first sought to clarify the effects of age and target characteristic on OCR gain in a normal population across the age span (n ¼ 60). We found that OCR gain is dependent on age, viewing distances, and target complexity, 19 as well as whether the target is head fixed or earth fixed. 20 Using an earth-fixed complex target at a distance of 1 m that has been shown to elicit higher gain in normal subjects, we recorded the eye movements of 18 patients with skew deviation and 18 normal participants by scleral search coil.…”
Section: Skew Deviationmentioning
confidence: 81%
“…43 We provided further evidence to confirm its existence by demonstrating that the magnitude of ocular counterroll responses is dependent on the age of subjects, viewing distance, target characteristics, and whether or not the target moves simultaneously with the head. 44,45 The ocular tilt reaction is a pathological synkinetic triad of skew deviation, ocular torsion, and head tilt. It has been attributed to lesions in the vestibular organ and its nerve, and central connections within the brainstem or cerebellum that asymmetrically disrupt the utriculo-ocular pathway.…”
Section: Pathophysiologymentioning
confidence: 99%
“…3,9 -11 The utricle normally mediates the static ocular counterroll (OCR) reflex which generates partially compensatory torsional eye movements during static head roll. [12][13][14] In a previous study, 5 we found that the OCR response was asymmetrically reduced in patients with skew deviation caused by cerebellar lesions. However, a definitive pattern could not be drawn because of the study's small sample size (n ϭ 3).…”
mentioning
confidence: 76%